ANALYSIS OF FINANCIAL PERFORMANCE AND INTERNET FINANCIAL REPORTING ACCESSIBILITY IN IMPROVING THE COMPLIANCE IN FINANCIAL INFORMATION DISCLOSURE - Anissa Windarti (Riset Akuntansi Keuangan, 2021)
Financial information disclosure is a public demand that must be fulfilled bythe local government. This study aimed to describe the financial performanceand IFR accessibility in improving compliance in financial informationdisclosure. There were 34 provincial governments in Indonesia taken as thepopulation of this study. The sample was taken using purposive samplingtechnique with the requirements of having e-government and accessiblewebsite until June 2018 and having a Financial Statement for the period of2015-2016. The data were analyzed using descriptive analysis withquantitative approaches. The results showed that the financial performanceduring the period of 2015-2016 did not show an evenly improved performancein each financial ratio. IFR accessibility in obtaining financial informationhas also not been maximally provided in the official website of the localgovernment. The level of compliance of financial information disclosures in2016 has decreased from which in 2015. This situation showed that theexisting financial performance and IFR accessibility had not been able toimprove compliance in disclosing financial information on the official localgovernment websites.